Analysis of causal pathogens of mulberry bacterial blight in samples collected from eight provinces of China using culturomics and metagenomic sequencing methods - Huang, Xinpeng; Yuan, Ting; Huang, Yuxin; Qazi, Izhar Hyder; Liu, Jiping (Frontiers in Plant Science, 2025)
Mulberry bacterial blight (MBB) is a complex and one of the devastating diseases of mulberry that causes serious reduction in the yield and quality of mulberry. In recent years, the transformation of sericulture industry, mulberry production system, and increasing seedling trade have resulted in the spread of MBB to different parts of China, posing a major economic threat to the farmers and industry. This study investigated the occurrence of MBB in eight provinces of China during years 2023 and 2024. The MBB disease samples were collected and the composition of the MBB pathogenic microbiome was analyzed by combining culturomics and metagenomic sequencing methods. A total of 498 bacterial strains were isolated and identified through culturomics, and then 109 suspected pathogen strains were preliminarily screened based on metagenomic sequencing data. Finally, 10 pathogens including, Pseudomonas syringae, P. fulva, P. fluorescens, Pantoea ananatis, Pectobacterium parvum, P. carotovorum, Flavobacterium fluviale, Citrobacter portucalensis, Klebsiella grimontii, Stenotrophomonas maltophilia, were identified through Koch’s postulates. Based on the distribution pattern of pathogens and the changes in the microbiome community of mulberry following infection with P. syringae, we infer that P. syringae, and P. fulva are important pathogens of MBB. In addition, based on the analysis of meteorological data, different bacteria showed adaptability to different environments, leading to differences in the pathogens of MBB under different climate conditions and latitudes. The data presented herein provides a foundation for understanding the occurrence, spatial distribution and pathogenic mechanism of MBB and its major pathogens.